OpenEHR and business intelligence in healthcare: an overview - Cunha, João Carlos Soares (2023)
Healthcare systems are a constant concern in today's society. The healthcare sector, like any other, collects a large amount of information on a daily basis. This information has recently been stored in electronic health records, the EHR. These records are a way to store a patient's information electronically, consequently improving its availability for better management in the institution. On the other hand, it is important to realise that there is an interoperability in this data, since there is a large interaction of various systems, and it is important to ensure interaction between these systems. To combat this interoperability problem, OpenEHR modelling emerges. To improve the management of the existing information in these records, it is interesting to integrate with Business Intelligence. Therefore, the objective of this article is to present an overview of OpenEHR and Business Intelligence systems, as more specific to health sector.